Bridging the Gap - Hvattum, Mari (Docomomo Journal, 2011)
On July 30, 1870, a visitor to the Niagara Falls noted glumly in his diary that “the impression of the waterfall was gripping, but not what I had expected”. Having traveled from Northern Europe to reach this scenic spot, the traveler - a railway engineer - was frankly disappointed. The landscape was flat and dreary, and only seen from very particular angles did the falls live up to their sublime reputation. What consoled the disillusioned tourist, however, were the many beautiful bridges built to accommodate traffic, commerce, and sightseeing around the falls: “The proud Clifton suspension bridge with its 1269’ span, 300’ above the river, was light and beautiful. The picturesque bridges across to Goat Island and “Three sisters” - all in pleasant harmony - give to the place a decidedly attractive character” he enthused. Regardless of its reputation as the most spectacular natural scenery in the world, to our railway engineer, Niagara was saved only by the sublime spectacle of the bridges.